Appetite and food intake results from phase I studies of anamorelin. Issue 5 (9th May 2019) - Blum, Robert A.; Mair, Stuart; Duus, Elizabeth M.
Abstract: Background: Loss of appetite and body weight are potentially devastating, highly prevalent cancer complications. The ghrelin receptor is a mediator of appetite and metabolism, and anamorelin is a novel, orally administered ghrelin receptor agonist. Effects on appetite and food intake may influence body‐weight gain but can be difficult to measure in multi‐site studies. Here, we summarize two single‐centre trials. Methods: Both trials were phase I, randomized, double‐blind, placebo‐controlled, partly/wholly crossover studies of healthy young adults. Study 102 tested single anamorelin doses of 1–20 mg. Assessments included post‐dose self‐ratings on 100 mm visual analogue scales for hunger, anticipated eating pleasure, and anticipated quantity of food consumption. Study 101 tested single 10, 25, and 50 mg doses. Assessments included the same scales plus caloric intake beginning 4 h post‐dose. Results: Study 102 treated 16 male subjects (mean age, 26.3 years). Mean hunger scores generally increased after all treatments, with significant differences from placebo ( P < 0.05) in the 5 mg anamorelin group at 0.5 and 1 h post‐dose (+8.2 and +13.2 mm). Results for other scales were similar. Study 101 treated nine male subjects (mean age, 26.3 years). Pooled findings for anamorelin 25 and 50 mg vs. placebo showed significant mean increases in hunger scores at all but 1 pre‐prandial time point, including the first assessment, 0.5 h post‐dose (+10.9 vs. +0.7 mm, P = 0.0077), and the last assessment, 4 h post‐dose (+32.7 vs. +7.0 mm, P = 0.0170), with a significant mean 18.4% increase vs. placebo in caloric intake ( P = 0.0148). Conclusions: In single‐centre studies of healthy adults, single anamorelin doses of 1–20 mg elicited modest increases in hunger, and single doses of 25 and 50 mg achieved significant increases in hunger and caloric intake. The findings are consistent with dose‐related weight gain reported in a prior phase I study as well as multi‐centre findings in cachectic cancer patients and expand the evidence supporting anamorelin as a potential intervention.